In situ identification strategy of thermoacoustic stability in annular combustors. (December 2018) - Rouwenhorst, Driek; Hermann, Jakob; Polifke, Wolfgang
In annular combustion systems, thermoacoustic eigenmodes can manifest as standing waves, traveling waves or some form in between. Which dynamic solution appears in a combustor depends on details, regarding the flow field and (unintentional) breaking of the cylindrical symmetry of the annular combustion system. When these details are unknown, the specific behavior cannot be predicted from the characteristics of a single burner. Due to the (nearly) degenerate nature of the acoustic solution, annular eigenmodes come in pairs with practically the same eigenfrequency. In order to identify the thermoacoustic modes, conventional analysis of a spectral peak from a measurement does not suffice, because the peak is a superposition of the two eigenmodes. A method has been proposed to identify the two eigenmodes of given azimuthal mode order from multiple simultaneous measurements around the circumference of the combustion system. Using output-only identification on the acoustic signals, it is possible to estimate the individual mode shapes, frequencies and growth rates of the co-existing eigenmode pair. In this work, the strategy is applied to experimental data from an annular combustor. A split in the growth rate pair is observed during stable operation, depending on the equivalence ratio and flame-to-flame distance. It shows that in situ identification of annular thermoacoustics can reveal subtle dynamic effects, which is useful for testing and online monitoring of annular combustors. The moment when instability occurs can be foreseen under prevailing conditions, with simultaneous identification of the azimuthal mode structure.